Research on Effective Strategies of College Physical Education Interactive Teaching Based on Machine Learning - Zhe Zhang; Yinghui Zhang (Applied Bionics and Biomechanics)
To master physical education courses, you must master a complete set of skills and knowledge. Most teachers still adopt traditional teaching forms, teacher centered, which has a negative impact on students. Because learners only passively participate in activities, it reduces students’ enthusiasm and focus to master skills. This study is aimed at comparing and contrasting the differences between modern interactive learning and traditional teaching strategies. We collect qualitative and quantitative results about the impact of these studies on students’ communication skills and understanding of relevant topics. The form of the noninteractive learning strategies explored in this study is the teaching system. This is a commonly used method and is still used in some institutions. Its limitations have led to the modernization of the education sector, especially in sports. This modernization brings about other forms of physical education, being student centered and more interactive. This form of interaction promotes the connection between teachers and students and promotes the transmission of feedback and the continuous improvement and novelty of activity forms. The interactive approach used in this study is the brainstorming method. Research has found it to generate constructive ideas and ideas. The specific process includes case study and Q & A, which is intuitive and clear, and can enhance the comprehensive understanding of the theme. The modernization of physical education curriculum brings many benefits; some of which will be listed in this paper. This study is aimed at promoting more display of students’ personality in modern physical education teaching with clear research conclusions. Let the students in the training interact with teachers and interact with the group, in the interaction to play their own greater initiative, enthusiasm. Let the relationship between students and teachers be more harmonious, and let the students’ physical quality get better development.